Effect of substrate moisture on the production of straw mushroom, Volvariella volvacea - Pani, B K; Chinara, N; Mohapatra, K B (Mushroom Research, 2018)
Straw mushroom (Volvariella volvacea) is extensively cultivated in Odisha as a profitable business enterprise. It is cultivated in cuboidal beds with layer spawning. Keeping in view the absence of any systematic research on the optimum moisture requirement of the substrate, an experiment was conducted to determine the effect of substrate moisture on the production of straw mushroom, Volvariella volvacea. Varied moisture content viz. 0 (dry straw without soaking), 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100 % were maintained in the substrate prior to spawning. It was revealed that soaked paddy straw with 60 % moisture sustained the highest yield of mushroom (1214.7 g, 12.1 % BE) compared to other treatments. Dry straw (without any soaking) failed to produce any fruiting body. The increase in moisture content from 10 to 60 % is directly proportional to the increase in yield. There was a gradual decline in yield as the moisture content was increased from 60 to 90 %. There was no fruiting in saturated moisture (100 %) condition. It has commonly been observed that the top layer of a straw bed, having the same moisture status as other layers, produces very sparse or no fruiting. This adversely affects the overall productivity of the bed. Therefore, another study was conducted, wherein, the moisture content of the top/covering layer was allowed to have different moisture levels such as 0 (dry straw, without soaking), 10, 20, 30, 40, 50 and 60 % whereas the remaining three layers contained 60 % moisture. It was revealed that 30 % moisture in the top layer was optimum to support maximum fruiting (463.7 g) on top leading to highest total production in the bed(1416.4g, 14.1 % BE).This was significantly higher than that of the normal practice(1140.7 g, 11.4 % BE) of having 60 % moisture in the top as well as other layers. The beds covered with dry straw produced only 10.4 g of fresh mushrooms leading to significantly lower overall productivity ( 938.4 g, 9.3 % BE).